The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/09546634.2016.1277177
|View full text |Cite
|
Sign up to set email alerts
|

Oral propranolol for infantile hemangiomas: a prospective study on the role of 48-hour Holter monitoring in additional safety assessment

Abstract: Oral propranolol for IHs does not remarkably affect heart rhythm including circadian variations throughout hospital initiation. Therefore, there is no necessity for Holter monitoring in additional safety assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…There were only 2 (2.9%) respiratory problems in our study, which may occur because children with a history of neonatal pneumonia are more likely to have respiratory disorder [27]; however, all patients included in our study did not have such a history. There was no asymptomatic hypotension or bradycardia observed; because we did not measure blood pressure in the routine follow-up [28, 29], hand-held pulse oximeter was used by parents for self-test and out-patient care. Pathoglycaemia was not found in the outpatient follow-up, but as mentioned above, the 2 cases of cold and sweaty hands and feet might have occurred owing to hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…There were only 2 (2.9%) respiratory problems in our study, which may occur because children with a history of neonatal pneumonia are more likely to have respiratory disorder [27]; however, all patients included in our study did not have such a history. There was no asymptomatic hypotension or bradycardia observed; because we did not measure blood pressure in the routine follow-up [28, 29], hand-held pulse oximeter was used by parents for self-test and out-patient care. Pathoglycaemia was not found in the outpatient follow-up, but as mentioned above, the 2 cases of cold and sweaty hands and feet might have occurred owing to hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…No AE, serious or not, was reported during drug initiation at the hospital, whatever the protocol used, as well as during the follow-up. No significant decrease in systolic blood pressure was observed, and the initial decrease in heart rate and diastolic blood pressure was moderate and not clinically relevant, as in the literature [38][39][40] . Similarly, previous studies have reported the safety of oral propranolol for the treatment of IH 41 and suggested not to extend cardiac monitoring beyond initiation period except for heart rate during following consultations 42 .…”
Section: Discussionmentioning
confidence: 56%
“…No AE, serious or not, was reported during drug initiation at the hospital, whatever the protocol used, as well as during the follow‐up. No significant decrease in systolic blood pressure was observed, and the initial decrease in heart rate and diastolic blood pressure was moderate and not clinically relevant, as in the literature 40–42 . Similarly, previous studies have reported the safety of oral propranolol for the treatment of IH 43 and suggested not extending cardiac monitoring beyond the initiation period except for heart rate during following consultations 44 .…”
Section: Discussionmentioning
confidence: 72%
“…No significant decrease in systolic blood pressure was observed, and the initial decrease in heart rate and diastolic blood pressure was moderate and not clinically relevant, as in the literature. [40][41][42] Similarly, previous studies have reported the safety of oral propranolol for the treatment of IH 43 and suggested not extending cardiac monitoring beyond the initiation period except for heart rate during following consultations. 44 In light of these results, an outpatient Hemangiol initiation protocol could be considered in selected and not at-risk patients, as suggested by Puttgen et al 45 This study supports the absence of relevance for a systematic pretherapeutic paediatric cardiology consultation.…”
Section: T a B L E 3 Serious Adverse Eventsmentioning
confidence: 92%